Exploring Indonesian Teachers' and Students' Perceptions and Practices of Translanguaging and Trans-Semiotizing in EFL Classrooms - Ronald Maraden Parlindungan Silalahi; Wulandari Santoso (Universitas Hamzanwadi, 2023)
The current trend of dynamic multilingualism in the field of applied linguistics has triggered the emergence of pedagogical approaches that aim to support and legitimate multilingual language practices. Translanguaging and trans-semiotizing are among the terms that have been widely used to describe the dynamic flows of discursive practices that involve one’s full semiotic repertoire to communicate and construct knowledge, which still remains unexplored in this context. This study aimed to investigate both university teachers and students’ perceptions of translanguaging and trans-semiotizing in English classrooms. Using observation, semi-structured interviews to five teachers and focus group discussion to seven students, the results of thematic analysis demonstrated that while the teachers seemed to expect the implementation of monolingual instruction, the students had a more positive view towards the utilization of multiple languages and semiotic signs in the classroom. It was also found out that translanguaging and trans-semiotizing served numerous pedagogical functions in enhancing students’ comprehension of the materials. Nevertheless, the ability to translanguage and trans-semiotize was not seen as a multilingual competence, but as a manifestation of one’s linguistic deficiency. This study suggests that translanguaging and trans-semiotizing should not merely be seen as a pedagogical tool, but these practices should also be legitimated and valued.